Synthesis of Quinoxalin-2(1H)-ones and Hexahydroquinoxalin-2(1H)-ones via Oxidative Amidation–Heterocycloannulation - Raghunadh, Akula; Tadiparthi, Krishnaji; Meruva, Suresh Babu; Murthy, V. Narayana; Rao, L. Vaikunta; Kumar, U. K. Syam (SynOpen, 2020)
A metal-catalyst-free synthesis of substituted quinoxalin-2-ones from 2,2-dibromo-1-arylethanone by employing an oxidative amidation–heterocycloannulation protocol is reported. The substrate scope of the reaction has been demonstrated and a possible mechanism for this reaction has also been proposed.
Keywords: oxidative amidation; heterocycloannulation; quinoxalin-2(1H)-one; 2,2-dibromo-1-arylethanone